Effects of a Benzalkonium Chloride Surfactant-Sodium Hypochlorite Combination on Microhardness and Mineral Content of Dentin - Aslantas, Eda Ezgi (2024)
This study aimed to investigate the impact of the combination of Benzalkonium chloride (BAC) and sodium hypochloride (NaOCl) and its application after ethylenediaminetetraacetic acid (EDTA) in root canal irrigation procedures on the microhardness and mineral content of dentin. Distal roots of mandibular third molars were embedded in auto-polymerizing acrylic resin, sectioned coronally to apically resulting in fifty-four root sections. Thirty sections underwent microhardness evaluation, and twenty-four sections were randomly chosen for mineral analysis. The microhardness assessment comprised three groups: Group 1 (2.5% NaOCl), Group 2 (2.5% NaOCl with 0.084% BAC), and Group 3 (2.5% NaOCl with 0.084 BAC post-17% EDTA). Initial and post-irrigation microhardness values were measured for each group. For mineral analysis, samples were categorized into four groups: distilled water, 2.5% NaOCl, 2.5% NaOCl with 0.084% BAC, and 17% EDTA+2.5% NaOCl with 0.084% BAC. X-ray photoelectron spectroscopy immediately measured magnesium, phosphorus, and calcium mineral contents on dentin surfaces post-irrigation. Results indicated a significant reduction in root dentin microhardness for all solutions (p<0.05). However, no statistically significant difference in the percentage of reduction was observed among the groups (p>0.05). XPS analysis revealed no significant disparity in dentin surface mineral content among the groups (p>0.05). In conclusion, the addition of Benzalkonium chloride to sodium hypochloride, either alone or after EDTA, did not induce a significant alteration in dentin microhardness or mineral content. These findings contribute to a nuanced understanding of dental irrigation protocols and their effects on dentin properties during endodontic procedures.